Proceedings of the 19th Annual International Conference on Supercomputing 2005
DOI: 10.1145/1088149.1088179
|View full text |Cite
|
Sign up to set email alerts
|

Power-aware resource allocation in high-end systems via online simulation

Abstract: Traditionally, scheduling in high-end parallel systems focuses on how to minimize the average job waiting time and on how to maximize the overall system utilization. Despite the development of scheduling strategies that aim at maximizing system utilization, parallel supercomputing traces that span long time periods indicate that such systems are mostly underutilized. Much of the time there is simply not enough load to keep the system fully utilized, although time periods do exist where system utilization level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The authors in (Horvath et al, 2007;Wang and Lu, 2008;Wang et al, 2009;Li et al, 2011) used DVFS techniques to save energy. Some works like the one presented in (Lawson and Smirni, 2005) dynamically adjust the number of CPUs in a cluster to operate in ''sleep'' mode when the utilization is low, others like in (Lang and Patel, 2010;Heo et al, 2011;Chakravarty and Sinha, 2013) switch the PMs from on to off. Bradley et al (2003;Guenter et al, 2011;Bobroff et al, 2007), the authors statistically analyze the workload data and examine how to minimize the power consumption using workload history.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in (Horvath et al, 2007;Wang and Lu, 2008;Wang et al, 2009;Li et al, 2011) used DVFS techniques to save energy. Some works like the one presented in (Lawson and Smirni, 2005) dynamically adjust the number of CPUs in a cluster to operate in ''sleep'' mode when the utilization is low, others like in (Lang and Patel, 2010;Heo et al, 2011;Chakravarty and Sinha, 2013) switch the PMs from on to off. Bradley et al (2003;Guenter et al, 2011;Bobroff et al, 2007), the authors statistically analyze the workload data and examine how to minimize the power consumption using workload history.…”
Section: Related Workmentioning
confidence: 99%
“…Distributed methods for RA such as market mechanism, compensation and coalition formation, were summarized in the survey by Wu et al [140]. Distributed solutions were also the focus of Laure et al [75,76] with a particular interest on data or data-centric Grids. Krauter et al [69] surveyed and categorized existing resource management systems (RMS) and identified open challenges.…”
Section: Brief Comparison With the Existing Surveys On Grid Resource mentioning
confidence: 99%
“…Some of the Grid features include different global administrative control over resources, existence of multiple Grid schedulers together with local schedulers, different performance characteristics of resources with respect to CPU especially, and storage system access [75,76]. Current research on novel dynamic RM and job scheduling [81] add more scalability, robustness and fault tolerance to the system by balancing high workload due to the dynamic realtime availability of high computational power of various Grid resources.…”
Section: Resource Managementmentioning
confidence: 99%
“…Lawson et al aim to decrease supercomputing center power dissipation powering down some nodes ( [17]). The EASY backfilling is used as the job scheduling policy.…”
Section: Related Workmentioning
confidence: 99%